2020
DOI: 10.1371/journal.pone.0234526
|View full text |Cite
|
Sign up to set email alerts
|

Foraging through multiple nest holes: An impediment to collective decision-making in ants

Abstract: In social insects, collective choices between food sources are based on self-organized mechanisms where information about resources are locally processed by the foragers. Such a collective decision emerges from the competition between pheromone trails leading to different resources but also between the recruiting stimuli emitted by successful foragers at nest entrances. In this study, we investigated how an additional nest entrance influences the ability of Myrmica rubra ant colonies to exploit two food source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…Using entrances from two opposite sites could have an influence on the foraging activity. For example, it was shown that for the red ant Myrmica rubra, the number of nest entrances influenced the collective foraging of the colony: multiple nest entrances reduced the foraging efficiency [42] but favored the simultaneous exploitation of several sources. It has been suggested that multiple entrances appear as a way for small-or medium-sized colonies to benefit from some of the advantages conferred by polydomy [38]-i.e., the simultaneous use of several nest sites by one colony-and T. crassispinus colony might use more than one nest (seasonal polydomy) [43].…”
Section: Discussionmentioning
confidence: 99%
“…Using entrances from two opposite sites could have an influence on the foraging activity. For example, it was shown that for the red ant Myrmica rubra, the number of nest entrances influenced the collective foraging of the colony: multiple nest entrances reduced the foraging efficiency [42] but favored the simultaneous exploitation of several sources. It has been suggested that multiple entrances appear as a way for small-or medium-sized colonies to benefit from some of the advantages conferred by polydomy [38]-i.e., the simultaneous use of several nest sites by one colony-and T. crassispinus colony might use more than one nest (seasonal polydomy) [43].…”
Section: Discussionmentioning
confidence: 99%
“…Many species of ants create their own transport and information processing networks using pheromone trails. These trails are created through foragers that leave the nest in search of food and upon returning with food, deposit pheromone trails on their way back to the nest (Beckers et al, 1992 ; Lehue & Detrain, 2020 ; Wendt et al, 2020 ). These trails encode quality: the better the food source, the more pheromone the successful foragers deposit.…”
Section: Facets Of Embodimentmentioning
confidence: 99%
“…For example, the information sharing between returning foragers to new recruits is an independent process at each nest entrance (Lehue et al, 2020 ). Therefore, having multiple nest entrances instead of one interferes with path optimisation, reducing the chances of finding food, establishing stable pheromone trails and effectively choosing the highest quality food source, resulting in a lower overall food gathering (Lehue et al, 2020 ; Lehue & Detrain, 2020 ). On the other hand, an increase in nest entrances facilitates the discovery of more food sites, which is useful for species harvesting many small, scattered packets of food, and exploiting more resources simultaneously is also a good bet-hedging strategy against losing resources, for example, to competing colonies or by depletion (Lehue et al, 2020 ; Lehue & Detrain, 2020 ).…”
Section: Facets Of Embodimentmentioning
confidence: 99%
“…One of the most complex collective efforts of these societies is foraging behavior (Anderson & Ratnieks, 1999; Bonabeau & Theraulaz, 1999; Laloi et al, 2000; Aredes et al, 2022). Social foraging in insects depends on individual behaviors triggered by positive and negative stimuli, which, according to their frequency and intensity, may amplify or attenuate different behaviors (Detrain & Deneubourg, 2008; Lehue & Detrain, 2020). In termites, social foraging behavior involves interactions among individuals of different castes and is essentially regulated by chemical signals released by nestmates and the food source (Costa‐Leonardo, 2002; Costa‐Leonardo et al, 2009; Traniello & Leuthold, 2000; Bagnères & Hanus, 2015; Leonhardt et al, 2016; Costa‐Leonardo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%